Засоби передачі прихованого смислу в англомовному художньому дискурсі: прагмакогнітивний аспект - Кузнєцова, Ірина Володимирівна; Кузнєцова, Ганна Валеріївна; Kuznietsova, I. V.; Kuznietsova, H. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті здійснено спробу обґрунтування доцільності такого напряму лінгвістичних досліджень, який розкриває прагматичні якості та когнітивне підґрунтя різних видів імпліцитного мовлення в англомовному художньому дискурсі. Ставиться завдання щодо виявлення всієї сукупності видів імпліцитного мовлення й дослідження засобів, які його актуалізують. The article presents an attempt to ground the expediency of linguistic research which discloses the pragmatic features and cognitive prerequisites of various types of implied speech in English belles-lettres discourse. The given approach is motivated by the analysis of a number of research pieces on the topic. The inadequate investigation of a number of related issues is pointed out, and namely, the absence of syste¬matization of the means of implied communication, an incomplete study of separate types of implied communication as well as some terminological gaps in the given linguistic sphere. Hence the topicality of pragmatic-cognitive approach to the study of implied communication is stated. The article deals with such types of implied speech as a special usage of phraseological units, a hint (allusion hint included) and additional sense nuances. The attempt to analyze the discursive qualities of the mentioned implied speech types on the material of the contemporary English belles-lettres texts is suggested. Perspective directions of further research on the topic are stated.
Means of Rendering Implicit Sense in English Belles-lettres Discourse: Pragmatic and Cognitive Aspect
Keywords: прагматика; pragmatics; когнітивний аспект; cognitive approach; імпліцитне мовлення; implied speech